The The Correlation Between Listening Comprehension and Speaking Skill of The Eleventh-Year Students of Senior High School - Anti Khusnul Khotima; Ruslin; Zul Aini Rengur; Dzakiah; Hijrah Syam (Universitas Islam Negeri Palopo, 2026)
Listening and speaking are interrelated language skills that play a crucial role in learning English as foreign language. The relationship between the two important because listening provides input that supports the development of student’s speaking skill. However, previous studies have generally focused on the general relationship between listening and speaking skills without examining their specific aspects in depth, and have been dominated by studies on university and junior high school students. Research on high school students in rural Indonesia with low English exposure remains limited, indicating a research gap. Therefore, this study focuses on this context to provide a more specific contribution to the study of listening and speaking skills. This study aims to determine the relationship between listening skills and speaking skills of grade XI students of Senior High School. The study population consisted of 230 students and a sample of 31 students from grade XI A was selected using a purposive sampling technique. Data were collected through listening and speaking tests and then analyzed using descriptive statistics and Spearman correlation tests with the help of SPSS software version 27. The results of the study showed that the average score for listening skills was 20.97, while the average score for speaking skills was 19.42. Based on the score range 0-25, these scores indicate that students have relatively high achievement because they are close to the maximum score. The results of the correlation analysis showed a value of rₛ = .899 with a significance of p < 0.001, which means there is a strong and significant positive relationship between listening and speaking skill. This finding indicates that the better students' listening comprehension, the better their speaking skill.